Building cost planning for the design team: Third edition - Jaggar, D.; Love, Peter; Smith, J.; Olatunji, O. (2016)
Cost management of all building projects has become increasingly important as clients in the public and private sector demand the highest quality cost planning services with accurate budgeting and cost control. All members of the design team must integrate their activities to ensure that a high quality project is delivered on time and within budget. This book considers building cost planning and cost control from the client and the design team's perspective, where all decisions whether concerned with design, cost, quality, time, value or sustainability are taken as being interrelated. The latest Royal Institute of British Architects (RIBA) Plan of Work and the New Rules of Measurement for Early Stage Estimating and Cost Planning issued by the Royal Institution of Chartered Surveyors (RICS) have been incorporated into this new text. The book follows the building design cost planning process from the crucial inception stages and then through all the design stages to the completion of the technical design, contract documentation and the tender. It provides a template for good cost planning practice. An essential addition to this third edition is the introduction of integrated design and documentation processes captured in building Information modelling (BIM), on-line cost databases and computerised methods of cost planning. The integrated approaches are explained and provide vital information and knowledge for practitioners involved in building projects. All stakeholders involved in development and design and client teams in public and private sector policy making and implementation need to understand the new approaches to design management processes and how cost planning and design approaches are adapting to using the new technology in practice. The interactive style, using in-text and review questions makes this ideal for students and practitioners alike in property, architecture, construction economics, construction management, real estate, engineering, facilities management and project management.